Persistence of psychotic symptoms as an indicator of cognitive impairment in methamphetamine users. (1st March 2015) - Chen, Chih-Ken; Lin, Shih-Ku; Chen, Yi-Chih; Huang, Ming-Chy; Chen, Tzu-Ting; Ree, Shao Chun; Wang, Liang-Jen
Highlights: Meth users with persistent psychosis and patients with schizophrenia show comparable cognitive profiles. Meth users with persistent psychosis have worse cognitive function than those without persistent psychosis. Cognitive function of the meth users without persistent psychosis and the healthy control subjects are similar. Among the meth users, the negative psychotic symptom correlated to cognitive performance. Abstract: Background: Prolonged exposure to methamphetamine (meth) has neurotoxic effects and impairs neurocognitive functions. This study aims to ascertain whether meth users who experience persistent psychosis suffer more severe cognitive impairment than those not experiencing persistent psychosis. Methods: This cross-sectional study includes 252 participants: 25 meth users without psychosis (METH − P), 50 with brief psychosis (METH + BP), and 56 with persistent psychosis (METH + PP), as well as 54 patients with schizophrenia and 67 healthy controls. The neurocognitive function and clinical psychopathology of each patient were evaluated with the Brief Assessment of Cognition in Schizophrenia (BACS) and the Brief Psychiatric Rating Scale (BPRS), respectively. Results: All cognitive domains evaluated with BACS (verbal memory, working memory, motor speed, verbal fluency, attention and processing speed, executive function, and composite scores) in METH + PP patients were similar to those in the schizophrenia patients and were worse than those in METH − P, METH + BP, and the healthy control subjects. Furthermore, cognitive functioning in meth users that did not experience persistent psychosis showed no statistically significant difference compared with the healthy control subjects. Among the meth users in this study, the negative symptom scores in the BPRS correlated to cognitive performance on the BACS, with the exception of motor speed. Conclusions: Meth users display heterogeneity in their psychotic symptoms and cognitive profiles. Therefore, persistent psychotic symptoms may denote a risk for cognitive decline among meth users. Further longitudinal studies should be performed in the future to clarify the causal relationship between cognitive deficits and the development of persistent psychosis.